MAGIC: Multi-User Advanced Graphic Immersive Configurator for Sustainable Customization of Complex Design Products—A Sailing Yacht Case Study - Saverio Piccininni; Mine Dastan; Fabio Vangi; Michele Fiorentino (Future Internet)
Modern design products are increasingly complex and emotionally significant, demanding versatile and collaborative customization. However, a literature and commercial review reveals a limited availability of flexible, multi-user, photorealistic Virtual Reality (VR) systems for product configuration. We introduce MAGIC (Multi-user Advanced Graphic Immersive Configurator), a collaborative platform combining realistic graphics with ergonomic validation using digital avatars, addressing the limitations of 2D visualization and existing tools. MAGIC is evaluated in a yacht design case study involving 30 participants in an immersive, co-located configuration of a sailing yacht to assess the system’s usability and the potential of VR for customizing complex products. Results show MAGIC’s feasibility in supporting multi-user configuration (100% success rate) and achieving a strong usability score (SUS = 80.83). User feedback highlights that high-quality graphics and additional content significantly enhance immersion and user engagement. However, encountered challenges with navigation methods and spatial perception indicate areas for improvement. MAGIC’s collaborative and immersive capabilities can be extended to other industries demanding proactive customer engagement in the customization of large, heavy products and ergonomic design. Moreover, by promoting prototype dematerialization and providing an interactive remote tool for end users, MAGIC offers potential environmental and economic benefits to boost the competitiveness of small and medium enterprises (SMEs).